Improving Patient Safety in Public Hospitals: Developing Standard Measures to Track Medical Errors and Process Breakdowns. Issue 8 (15th December 2021) - Ackerman, Sara L.; Gourley, Gato; Le, Gem; Williams, Pamela; Yazdany, Jinoos; Sarkar, Urmimala
Abstract : Objective: The aim of the study was to develop standards for tracking patient safety gaps in ambulatory care in safety net health systems. Methods: Leaders from five California safety net health systems were invited to participate in a modified Delphi process sponsored by the Safety Promotion Action Research and Knowledge Network (SPARKNet) and the California Safety Net Institute in 2016. During each of the three Delphi rounds, the feasibility and validity of 13 proposed patient safety measures were discussed and prioritized. Surveys and transcripts from the meetings were analyzed to understand the decision-making process. Results: The Delphi process included eight panelists. Consensus was reached to adopt 9 of 13 proposed measures. All 9 measures were unanimously considered valid, but concern was expressed about the feasibility of implementing several of the measures. Conclusions: Although safety net health systems face high barriers to standardized measurement, our study demonstrates that consensus can be reached on acceptable and feasible methods for tracking patient safety gaps in safety net health systems. If accompanied by the active participation key stakeholder groups, including patients, clinicians, staff, data system professionals, and health system leaders, the consensus measures reported here represent one step toward improving ambulatory patient safety in safety net health systems.